Widespread occurrence of structurally diverse tetraether membrane lipids: Evidence for the ubiquitous presence of low-temperature relatives of hyperthermophiles - Schouten, Stefan (The National Academy of Sciences, 2000)
Isoprenoid glycerol dialkyl glycerol tetraethers (GDGTs) and branched glycerol dialkyl diethers are main membrane constituents of cultured hyperthermophilic archaea and eubacteria, respectively, and are found in environments with temperatures >60°C. Recently, we developed a new technique for the analysis of intact core tetraether lipids in cell material and sediments. The application of this technique to recent sediments shows that known and newly identified isoprenoid and branched GDGTs are widespread in low-temperature environments (<20°C) and are structurally far more diverse than previously thought. Their distribution indicates the ubiquitous environmental presence of as yet uncultivated, nonthermophilic organisms that may have independently evolved from hyperthermophilic archaea and eubacteria. The structures of some of the new GDGTs point to the hybridization of both typical archaeal and eubacterial biosynthetic pathways in single organisms.